Anti-Leishmanial Activity of Iraqi Plant Gundelia Tournefortii and Isolation of Beta-Sitosterol - Razaq, Zainab Mizher; Dawood, Yessar A.; Jalil, Thukaa Z. Abdul (Academia Open, 2025)
Background: Herbal medicine remains a significant focus in contemporary pharmacological research due to its therapeutic benefits and low side effects. Specific Background: Gundelia tournefortii is recognized for its medicinal potential, yet its anti-leishmanial properties are underexplored. Leishmaniasis, particularly caused by Leishmania donovani, remains a critical health challenge with no available vaccines and limited treatment options. Knowledge Gap: Despite the ethnobotanical use of G. tournefortii, its phytoconstituents, especially beta-sitosterol, have not been thoroughly investigated for anti-leishmanial activity. Aims: This study aimed to isolate beta-sitosterol from the oil extract of Iraqi G. tournefortii and evaluate the anti-leishmanial efficacy of two different extracts against Leishmania tropica and Leishmania donovani, in comparison to the standard drug, pentostam. Results: Beta-sitosterol was successfully isolated via HPLC at a concentration of 98.08 ppm. The oil extract showed superior efficacy, with IC₅₀ values of 0.042 mg/ml for L. tropica and 0.00127 mg/ml for L. donovani. Novelty: This research represents the first report on the isolation of beta-sitosterol from Iraqi G. tournefortii and its significant anti-leishmanial activity. Implications: The findings support the potential of G. tournefortii oil extract as a natural source for developing new anti-leishmanial therapies, particularly due to its sterol and triterpene content. Highlights: First isolation of beta-sitosterol from Iraqi G. tournefortii. Oil extract shows high efficacy against L. donovani. Potential for developing plant-based leishmaniasis treatment. Keywords: Gundelia Tournefortii, Leishmania Tropica, Leishmania Donovani, Pentostam, IC50